Cerro de Amalucan: willingness to pay (WTP) of a tariff by the contingent valuation methoddouble limit - Torres Ramirez, Ramiro; Martínez Damián, Miguel Ángel; Valdivia Alcalá, Ramón; González Juárez, Araceli; Sandoval Romero, Fermín; Torres Ramirez, Ramiro; Martínez Damián, Miguel Ángel; Valdivia Alcalá, Ramón; González Juárez, Araceli; Sandoval Romero, Fermín (Corporación Universitaria Americana, 2023)
Introduction: The pressure on green areas within large cities have had in the world negative effects for the population, the Cerro de Amalucan Park (PCA) is no exception has been at risk of being eliminated, from its little more than 200 hectares registered in the 20's to the current 74 hectares, therefore it is important to conduct studies on this ecological reserve to generate information that helps to understand the importance of the PCA. Objective: The objective is to estimate the average Willingness to Pay (WTP) of visitors for the implementation of a fee for the execution of a management and conservation program in the area using the Double Boundary (DL) Contingent Valuation Method (CVM) to determine the economic value of PCA and general recommendations for obtaining resources based on socioeconomic aspects (income, education, sex). Methodology: Using a simple random sample, a sample of 118 surveys was determined, based on which information was collected through surveys conducted in the city of Puebla and its metropolitan area. Results: Linear and logarithmic models were used. The WTP's were estimated and the best one was selected with a result of $10 MXN ($0.51 DLS) and the result is affected by the socioeconomic and environmental perception variables. Conclusions: It is concluded that there is a willingness of visitors to pay a fee to access the PCA.